Characterisation of Thermal Inertia in University Buildings Using Continuous Temperature Monitoring Data - García Monge, Miguel; Zalba Nonay, Belén; Guillén-Lambea, Silvia (Jornada de Jóvenes Investigadores del I3A, 2025)
The article presents a methodology for analysing the thermal behaviour of buildings and HVAC systems using temperature data. Thermal inertia was assessed by calculating the rate of indoor temperature increase (°C/h) during the heating period (5–9 a.m.) with MATLAB, to improve HVAC scheduling, enhancing energy efficiency, IEQ, and grid interaction.